Anadenanthera Colubrina vell Brenan: anti-Candida and antibiofilm activities, toxicity and therapeutical action - Diego Romário Silva; Pedro Luiz Rosalen; Irlan Almeida Freires; Janaína de Cássia Orlandi Sardi; Rennaly Freitas Lima; Josy Goldoni Lazarini; Tereza Karla Vieira Lopes da Costa; Jozinete Vieira Pereira; Gustavo Pina Godoy; Edja Maria Melo de Brito Costa (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: We evaluated the antifungal and antibiofilm potential of the hydroalcoholic extract of bark from Anadenanthera colubrina (vell.) Brenan, known as Angico, against Candida spp. Antifungal activity was evaluated using the microdilution technique through the Minimum Inhibitory and Fungicide Concentrations (MIC and MFC). The antibiofilm potential was tested in mature biofilms formed by Candida species and analyzed through the counting of CFU/mL and scanning electron micrograph (SEM). In vivo toxicity and therapeutic action was evaluated in the Galleria mellonella model. The treatment with the extract, in low doses, was able to reduce the growth of planktonic cells of Candida species. MIC values range between 19.5 and 39 µg/mL and MFC values range between 79 and 625 µg/mL. In addition was able to reduce the number of CFU/mL in biofilms and to cause structural alteration and cellular destruction, observed via SEM. A. colubrina showed low toxicity in the in vivo assay, having not affected the viability of the larvae at doses below 100mg/kg and high potential in the treatment of C. albicans infection. Considering its high antifungal potential, its low toxicity and potential to treatment of infections in in vivo model, A. colubrina extract is a strong candidate for development of a new agent for the treatment of oral candidiasis.